Novel platform for engineering stable and effective vaccines against botulinum neurotoxins A, B and E - Liu, Yang; Liu, Xiaoyu; Chen, Weiwei; Yu, Yunzhou; Meng, Jianghui; Wang, Jiafu (Frontiers in Immunology, 2024)
Botulinum neurotoxin (BoNT), produced by Clostridium botulinum, is the most toxic protein known, capable of causing severe paralysis and posing a significant bioterrorism threat due to its extreme lethality even in minute quantities. Despite this, there are currently no FDA-approved vaccines for widespread public use. To address this urgent need, we have developed an innovative vaccine platform by fusing the neuronal binding domain of BoNT/E (Hc/E) with core-streptavidin (CS), resulting in a stable CS-Hc/E vaccine. Mice vaccinated with CS-Hc/E exhibited superior antibody titers compared to those receiving Hc/E alone. To develop a trivalent vaccine against BoNT/A, BoNT/B, and BoNT/E-key contributors to the vast majority of human botulism-we conjugated CS-Hc/E with a biotinylated atoxic chimeric protein incorporating neutralizing epitopes from BoNT/A and BoNT/B. This chimeric protein includes the binding domain of BoNT/A, along with the protease-inactive light chain and translocation domains of BoNT/B. The interaction between CS and biotin formed a stable tetrameric antigen, EBA. Vaccination with EBA in mice elicited robust antibody responses and provided complete protection against lethal doses of BoNT/A, BoNT/B, and BoNT/E. Our findings highlight EBA's potential as a stable and effective broad-spectrum vaccine against BoNT. Moreover, our technology offers a versatile platform for developing multivalent, stable vaccines targeting various biological threats by substituting the BoNT domain(s) with neutralizing epitopes from other life-threatening pathogens, thereby enhancing public health preparedness and biodefense strategies.